FEN1 Status and Its Correlation with Clinicopathologic Characteristic in Colorectal Cancer - Guo, Yundi; Du, Zixuan; Zhou, Yuanshuai; Sun, Haijun; Liang, Rui; Sun, Min-Xuan; Tang, Zaixiang; Liu, Song-Bai (Combinatorial Chemistry & High Throughput Screening, 2022)
Objective: The goal of this study was to investigate the status of FEN1 in colorectal cancer (CRC) and determine the potential correlation between FEN1 expression level and clinicopathological parameters in CRC patients. Methods: Expression of FEN1 in CRC tissue on tissue microarray was detected using immunohistochemistry (IHC). The relationship between FEN1 expression status and clinicopathologic characteristics of CRC was analyzed by the Chi-square test. The survival data of TCGA Colon Cancer (COAD) were obtained from ucsc xena browser (https://xenabrowser.net/). Patients were separated into higher and lower expression groups by median FEN1 expression. The association with prognosis of CRC patients was determined by Kaplan-Meier survival analysis with Log-rank test. Results: FEN1expression level and cellular localization had wide variability among different individuals; we classified the staining results into four types: both positive in nucleus and cytoplasm, both negative in nucleus and cytoplasm, only positive in the nucleus, only positive in the cytoplasm. Moreover, FEN1 expression status only correlated with patient’s metastasis status, and the patients in the NLCL group showed more risk of cancer cell metastasis. Conclusion: Our results indicate that FEN1 expression level and cellular localization had wide variability in CRC and is not a promising biomarker in CRC.
Keywords: IHC